PENGARUH KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA PADA PT. MITRA AGUNG SWASTIKA - Nasution, Muhammad Ilham (Jurnal Mahkota Bisnis (Makbis), 2025)
This study aims to determine the effect of communication and organizational culture on employee job satisfaction at PT. Mitra Agung Swastika. The approach used in this study is to use an associative approach. The place in the preparation of this research was carried out at PT. Mitra Agung Swastika which is located at Jl. Gatot Subroto No. 30., Medan Petisah, Medan. This company is engaged in the field of fitness. The population and sample in this study were all employees of PT. Mitra Agung Swastika, totaling 80 people. This research instrument uses validity and reliability tests. Data analysis techniques use multiple regression tests and hypothesis tests and tests are carried out using SPSS Version 25 software. The results of the study indicate that communication influences employee job satisfaction at PT. Mitra Agung Swastika with a t-test value of 6.445> t table 1.991. Organizational Culture variables have a positive and significant effect on employee job satisfaction at PT. Mitra Agung Swastika with a calculated t value of 5.102> t table 1.991. Simultaneously, it is known that the significance value of 0.000 is smaller than 5% or 0.05 or the Fcount value = 199.448>Ftable 3.115 (df1 = k-1 = 3-1 = 2) while (df2 = n – k (80 – 3 = 77). Thus, it can be concluded that all independent variables, namely Communication and Organizational Culture, have a positive and significant effect on Employee Job Satisfaction at PT. Mitra Agung Swastika.